Elevated Nesfatin-1 and Altered Reproductive Hormones in Polycystic Ovary Syndrome: A Comparative Case-Control Study. - ghazi Mohammed, Zainab; Ali Farman, Hassan (Journal of Neonatal Surgery, 2025)
Background and Aim: Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder affecting reproductive-age women, characterized by hyperandrogenism, ovarian dysfunction, and metabolic disturbances. Nesfatin-1, a neuropeptide involved in appetite regulation, has been proposed as a potential link between metabolic and reproductive dysfunction. This study aimed to investigate the relationship between serum Nesfatin-1 levels, hormonal changes, and anthropometric parameters in women with PCOS. Methods: A cross-sectional, case-control design was employed, including 60 women diagnosed with PCOS based on the Rotterdam criteria and 30 age-matched healthy controls. Anthropometric measurements were recorded, and fasting blood samples were collected during the early follicular phase. Luteinizing hormone, follicle-stimulating hormone, estradiol, progesterone, testosterone, and Nesfatin-1 were quantified using validated immunoassays. Between-group differences were assessed via independent samples t-tests or Mann–Whitney U tests, and correlation analyses were conducted to explore potential associations. Results: Participants with PCOS demonstrated significantly elevated body mass index, prolonged menstrual cycles, and higher levels of luteinizing hormone and testosterone compared with controls, alongside reduced follicle-stimulating hormone and estradiol. Serum Nesfatin-1 concentrations were markedly greater in the PCOS group compared to healthy participants (580.182 ± 133.691 vs. 266.232 ± 69.0825 pg/mL; p<0.001). Nesfatin-1 showed positive correlations with testosterone (R=0.264, p=0.048) and estradiol (R=0.279, p=0.031). Conclusion: These findings underscore the role of Nesfatin-1 as a potential biomarker linking metabolic dysregulation and reproductive abnormalities in PCOS. The elevated Nesfatin-1 levels may reflect a compensatory neuroendocrine response to hyperandrogenemia and insulin resistance. Future longitudinal and mechanistic studies are necessary to elucidate Nesfatin-1’s pathophysiological significance and evaluate its therapeutic implications in managing PCOS.